2021
DOI: 10.1093/nsr/nwab103
|View full text |Cite
|
Sign up to set email alerts
|

Application of smog chambers in atmospheric process studies

Abstract: The smog chamber experimental systems, which have been widely used in laboratory simulation for studying atmospheric processes, are comprehensively reviewed in this paper. The components, development history, main research topics, and main achievements of smog chambers are introduced. The typical smog chambers in the world, including their volumes, wall materials, light sources, and features, are summarized and compared. The key factors of smog chambers and their influences on the simulation of the atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 115 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…These results indicated that there may be other sources of hydroxyl radicals in the smog chamber. For example, the heterogeneous generation of HONO on the chamber wall, which was recognized as an important source of hydroxyl radicals in the chamber, 46 may trigger the oxidation of SO 2 to gaseous H 2 SO 4 and then lead to NPF. However, in the presence of TiO 2 (Figure 2b), the particle number concentration and GMD increased to 6.43 × 10 4 cm −3 and 30 nm, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These results indicated that there may be other sources of hydroxyl radicals in the smog chamber. For example, the heterogeneous generation of HONO on the chamber wall, which was recognized as an important source of hydroxyl radicals in the chamber, 46 may trigger the oxidation of SO 2 to gaseous H 2 SO 4 and then lead to NPF. However, in the presence of TiO 2 (Figure 2b), the particle number concentration and GMD increased to 6.43 × 10 4 cm −3 and 30 nm, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The close contact of stacked samples brings substantial uncertainty to the experiment. Therefore, smog chamber [77][78][79] and individual particle analysis methods [80][81][82][83][84] have become popular in atmospheric heterogeneous reaction research in recent years. Smog chamber and individual particle analysis methods utilize non-contacting or suspended particles, which can truly reflect the heterogeneous reaction process on the surface of particles in the actual atmospheric environment, to obtain accurate kinetic parameters that reflect the real-life conditions of the atmosphere.…”
Section: Surface Heterogeneous Reactions Of Ampmmentioning
confidence: 99%
“…[16][17][18][19] What is more, NO 3 − is a severe N-containing water pollutant due to the use of nitrogenous fertilizer, discharge of industrial wastewater, and combustion of fossil fuel, which poses a great threat to natural environment. [20][21][22] In this regard, NO 3 RR process would also contribute to environmental protection.…”
Section: Introductionmentioning
confidence: 99%